Independent associations of serum calcium with or without albumin adjustment and serum phosphorus with nonalcoholic fatty liver disease: results from NHANES 1999-2018 - Qi, Haolong; Wang, Bin; Zhu, Lei (Frontiers in Endocrinology, 2024)
Background The associations of serum calcium and phosphorus with nonalcoholic fatty liver disease (NAFLD) remain unclear. In addition, there may be an effect of albumin correction on the association between serum calcium and NAFLD. We aimed to explore these relationships in the National Health and Nutrition Examination Survey (NHANES). Methods Eligible adult individuals from NHANES 1999-2018 were recruited for the study. We explored the associations of serum calcium, albumin-adjusted serum calcium, and serum phosphorus with NAFLD in multivariable-adjusted regression models. In addition, restricted cubic spline (RCS), stratified analysis, and multiple sensitivity analyses were used for further elaboration. Results The study sample consisted of 20,900 participants, with an observed NAFLD prevalence of 44.65%. Fully adjusted models indicated that serum calcium was inversely associated with NAFLD (odds ratio [OR] and 95% confidence interval [CI] = 0.70 (0.62, 0.78), p<0.0001), whereas albumin-adjusted serum calcium was positively associated with NAFLD (OR and 95% CI=1.59 (1.41, 1.79), p<0.0001). RCS modeling indicated that serum calcium without and with albumin adjustment was linearly(p nonlinear = 0.083) and nonlinearly (p nonlinear < 0.0001) associated with NAFLD, respectively, whereas serum phosphorus showed a U-shaped relationship with NAFLD(p nonlinear < 0.0001). Gender is a significant influence in all associations, and other variables may also have an effect. Sensitivity analyses indicated that these associations were independent of additional significant confounders. Conclusion Serum calcium and phosphorus were significantly associated with the development of NAFLD. These findings suggest the potential clinical significance of serum calcium/phosphorus and albumin levels in individuals at high risk for NAFLD. Our study supports the potential role of serum calcium/phosphorus homeostasis in the pathophysiology of NAFLD and could serve as NAFLD-related biomarkers.